Influence of the location of drilling fluid loss on wellbore temperature distribution during drilling. (1st April 2022) - Zhang, Zheng; Wei, Yongqi; Xiong, Youming; Peng, Geng; Wang, Guorong; Lu, Jingsheng; Zhong, Lin; Wang, Jingpeng
Abstract: Circulation loss can occur at different positions during drilling, which has different effects on the wellbore temperature distribution. To ensure the safety and effectiveness of the drilling process, it is necessary to study the influence of circulation loss at different positions on the wellbore temperature distribution. In this study, we established mathematical models of wellbore temperature distribution corresponding to different situations in which circulation loss occurred and obtained the wellbore temperature distribution for each situation. When circulation loss occurred in the one-dimensional region, the annulus drilling fluid temperature at the circulation loss position changed suddenly; when it occurred in the two-dimensional region, the wellbore temperature at the circulation loss position was significantly disturbed. Under other conditions unchanged, as the circulation loss occurred closer to the bottom hole, the lower the wellbore temperature became at the same well depth. After circulation loss occurred, the formation temperature in the circulation loss area decreased significantly. The difference between the wellbore temperature distribution curve after circulation loss occurs and the wellbore temperature distribution curve when no circulation loss occurred can be used to monitor the location of the circulation loss in real time. Highlights: The wellbore heat transfer mechanism of leakage in different areas is analyzed. The calculation models for circulation loss in different areas are established. The wellbore temperature law of circulation loss in different areas is obtained. The method of real-time monitoring the location of circulation loss is obtained.